The Level of Organizational Citizenship Behavior among College Members of the Physical Education and Sports Sciences Department from their Students' Perspective - Mohammed, Safad Mudhafar (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2024)
Organizational citizenship behavior (OCB) plays a pivotal role in fostering a positive and conducive learning environment in educational institutions. This study investigated the level of OCB among college members of the Physical Education and Sports Sciences Department at the University of Zakho from the perspective of their students. Using a quantitative, descriptive approach, structured questionnaires were administered to a diverse sample of 159 students, varying in sex, study shift, and year of study.  The findings revealed a significant acknowledgment of OCB among department members, as perceived by their students, indicating the positive impact of such behaviors on the overall academic climate. Interestingly, no statistically significant difference was observed in OCB perceptions between male and female students, which suggests an inclusive and equitable learning experience. However, a notable difference emerged between students attending morning and evening study shifts, highlighting the potential influence of factors, such as faculty availability and resource allocation. Furthermore, the study explored variations in OCB perceptions across different years of study, with fourth-year students reporting the highest mean score, potentially attributable to cumulative exposure and interactions with faculty members. However, these differences were not statistically significant, indicating a relatively consistent perception of OCB across academic progressions. This study contributes to a broader understanding of OCB in academic settings and its potential impact on overall learning experience. It provides valuable insights into fostering a culture of citizenship behavior within educational institutions and offers recommendations for professional development initiatives and targeted interventions to enhance OCB across various study programs.